Automating Jenkins with Python - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Apply DevOps principles to Jenkins by automating tasks using the Jenkins API with Python. Create a powerful command-line tool with the Click framework to harness the API and trigger remote jobs with a simple invocation. Using code (and Python in this case) to automate frequent tasks is an import DevOps principle that you should apply whenever possible. Some of the concepts in this video are covered in the Python For DevOps book. Learn how to identify core concepts when trying to automate something like Jenkins, like identifying the API access, authorization, and the possibility of finding a helper library to make things easier. your Machine Learning model by following core best-practices of MLOps. Topics include: * Setup a main Jenkins instance with Docker, using the official Jenkins LTS image. * Create a user with an API token, so that it is authorized to operate Jenkins. * Use a Jupyter notebook to try out the API using Python and figure out concepts that can be applied later * Create a command-line tool using the Click framework to quickly trigger Jenkins jobs. Useful links: * Jenkins LTS Docker image documentation * Official Jenkins LTS Docker image * Python-Jenkins library documentation * Python-Jenkins Library * Python for DevOps Book.